2021
DOI: 10.33194/rper.2021.176
|View full text |Cite
|
Sign up to set email alerts
|

A Presença Da Família Nos Hospitais Em Tempos De Pandemia E O Paradoxo Da Segurança Do Doente

Abstract: Introdução: Devido à pandemia por COVID-19, para garantir a segurança dos cuidados de saúde e conter a sua transmissão, foram adotadas medidas restritivas que afastaram as famílias dos doentes hospitalizados. Tais medidas trouxeram implicações. Objetivo: analisar, a partir dos discursos dos enfermeiros especialistas em enfermagem de reabilitação (EEER), as vantagens, desvantagens e contextos da presença da família nos hospitais, à luz da segurança do doente, em contexto pandémico. Metodologia: Estudo qualitati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Post-SCI, the recovery phase relies heavily on family support [18,19]. Fear and anxiety among inpatients in this phase may be exponentiated when, for safety reasons, the environment calls for less in-person contact and increased social distancing, such as that experienced during the pandemic of COVID-19 [20]. As in this study, the family's absence from the hospital brought feelings of isolation, and although virtual contact does not replace the real world, using technology to maintain contact with relatives was considered necessary [21].…”
Section: Discussionmentioning
confidence: 99%
“…Post-SCI, the recovery phase relies heavily on family support [18,19]. Fear and anxiety among inpatients in this phase may be exponentiated when, for safety reasons, the environment calls for less in-person contact and increased social distancing, such as that experienced during the pandemic of COVID-19 [20]. As in this study, the family's absence from the hospital brought feelings of isolation, and although virtual contact does not replace the real world, using technology to maintain contact with relatives was considered necessary [21].…”
Section: Discussionmentioning
confidence: 99%
“…During the pandemic period, we found that the nurses’ actions were strongly influenced by the view of the family as a potential disseminator of infection. They assessed family presence more negatively than positively in terms of maintaining safety, an understanding that was not always supported by the available evidence [ 10 , 11 , 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%